Measuring residential water affordability and basic water needs in South Africa - Akhona Mgwele; Hiywot Menker Girma; Johane Dikgang (ZBW - Leibniz Information Centre for Economics, 2021)
Designing a desirable block tariff structure for residential water use has been a challenging task for regulated utilities. In this study, we investigated whether the existing increasing block tariff design addresses the issue of affordability, especially for lower-income groups. Using the South African NIDS household-level panel data and municipal tariff data, we estimated household demand for water using a Stone-Geary specification. The Stone-Geary functional form allows price elasticity of demand to vary with quantity consumed and allows for the estimation of a basic threshold level of consumption below which demand is price inelastic. Truncated and quantile regressions were run to observe the impact of the different socio-economic variables on different categories of water-consumption and income levels. The results show that in general, the first block (i.e., 6 000 litres) of consumption set by water utilities does not represent a basic water need. The `lifeline' or subsistence portion of water is found to be 11.51 kl of water per household per month. Moreover, when considering the poorest or low-income households, water charges raise affordability concerns in a number of important water-utility areas. Basic water is not affordable as the proportion of household income that must be spent to acquire it is high. Any household with an income of 398 or less must spend a significant proportion of its income (above 5.88%) to receive the subsistence amount of water. Furthermore, a number of socio economic and environmental factors are found to affect the demand for water, and these will help in employing tailored economic and technological interventions for efficient utilization of water.
Keywords: H41; I30; L32; Q25; 330; demand; equity; lifeline; increasing block tariff; water affordability